Active Compounds of Usnea Lichen and Their Potential as Pharmaceutical Raw Materials: A Review of Phytochemistry and Pharmacological Activities - Musdalifah, A.; Nurul Inaya Muhtar (Science Tech Group, 2025)
Lichens represent a unique symbiotic system and an important yet relatively underexplored source of bioactive natural products. Among them, the genus Usnea has attracted considerable scientific interest due to its chemically diverse secondary metabolites and wide range of pharmacological activities. However, current knowledge integrating phytochemical diversity, pharmacological mechanisms, and safety considerations remains fragmented. Therefore, this review aims to systematically summarize the major bioactive compounds identified in Usnea species and critically evaluate their pharmacological potential as pharmaceutical raw materials. Particular attention is given to polyketide-derived metabolites, including usnic acid, depsides, and depsidones, which exhibit diverse phenolic structures and contribute to antimicrobial, antioxidant, anti-inflammatory, and anticancer activities through mechanisms such as membrane disruption, free radical scavenging, modulation of inflammatory pathways, and apoptosis induction. Furthermore, toxicity concerns, especially hepatotoxicity associated with high-dose usnic acid, are discussed to highlight the need for improved safety evaluation and formulation strategies. The exploration of Usnea-derived natural products also supports global health initiatives, particularly the Sustainable Development Goals (SDGs), including SDG 3.4 (reducing premature mortality from non-communicable diseases) and SDG 3.b (promoting research and development of new medicines). Overall, Usnea represents a promising source of bioactive compounds for sustainable natural product-based pharmaceutical development.